Efficacy of decompression combined with transpedicular screw fixation in mixed lumbar stenosis. Case report - Maksim I. Gaydash; Changsu Lee; Mikhail G. Bashlachev; Mikhail G. Zonov; Hayder N. Akif (ZAO "Consilium Medicum", 2024)
Degenerative stenosis is a common pathology of the lumbar spine, however, there is currently no consensus on the clinical significance of neuroimaging findings and management tactics for such patients. In this regard, the issues of diagnosis and treatment have been causing discussions among doctors of both therapeutic and surgical profiles for many years. The article presents an observation of a 65-year-old patient with mixed lumbar stenosis, in whom surgical intervention in the form of decompression and transpedicular screw fixation led to a complete regression of pain, motor disorders and a significant improvement in functional condition. The issues of diagnosis, conservative and surgical treatment of mixed lumbar stenosis are discussed.